Upaya Meningkatkan Hasil Belajar Matematika Melalui Model Kooperatif Tipe Numbered Heads Together di Kelas V SD Mata Pelajaran Bangun Ruang - Setiyawan, Hery; Anggraini, Dilla Puspa; Dwi Maharani, Putri Aprilia; Hasanah, Lailatul; Nabilah, Qonita Ayu; Kurniasih, Anisah (Indo-MathEdu Intellectuals Journal, 2025)
The Numbered Heads Together (NHT) model is a cooperative learning model where students are divided into small groups and each member is given a number. This study aims to determine the effect of the Numbered Heads Together (NHT) cooperative learning model in fifth grade students of spatial geometry. This study is a Classroom Action Research (CAR) conducted in two cycles. The research subjects consisted of 20 fifth grade elementary school students. Data collection techniques used include observation, learning outcome tests, and document collection. The techniques used in this study were normality tests, homogeneity tests, and t-tests. The results showed that the implementation of the Numbered Heads Together (NHT) model successfully improved student learning outcomes. This can be seen from the increase in the average student score when comparing the control class with the experimental class. In addition, the NHT model also contributed to increased student participation in discussions and understanding of spatial geometry concepts. Thus, the Numbred Heads Together (NHT) cooperative learning model has proven effective in improving student learning outcomes in mathematics.